1975
DOI: 10.1017/s0022112075002169
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of low Reynolds number secondary streaming effects associated with an oscillating viscous flow in a curved pipe

Abstract: This paper deals with nonlinear streaming effects in an oscillating fluid in a curved pipe. The secondary steady velocity field in the cross-sectional plane of the pipe is studied in detail. Our experimental results are compared with the theory of Lyne (1970; that part of his theory which is valid for Reynolds numbers Rs [Lt ] 1) and the theory of Zalosh & Nelson (1973). On the basis of these comparisons we conclude that the theories are in practice valid for higher Reynolds numbers Rs than was formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…His analytical study showed that a new vortex pair appears and coexists with Dean cells (Lyne instability). Zalosh and Nelson [6] obtained the same results, and later experimental work of Bertelsen [7] confirmed previous work. Sudo et al [8] characterized the secondary flow by the Womersley number in fully developed oscillatory flow and classified secondary flow structures into five patterns.…”
Section: Introductionsupporting
confidence: 82%
“…His analytical study showed that a new vortex pair appears and coexists with Dean cells (Lyne instability). Zalosh and Nelson [6] obtained the same results, and later experimental work of Bertelsen [7] confirmed previous work. Sudo et al [8] characterized the secondary flow by the Womersley number in fully developed oscillatory flow and classified secondary flow structures into five patterns.…”
Section: Introductionsupporting
confidence: 82%
“…As a increases to 6 the centres move towards the inside of the bend and remain there a t a = 10. This thickening of the vortex core on the inside of the curve was attributed to finite-curvature effects by Bertelsen (1975), but from these results it would appear to depend on G when a 2 6. The full time-dependent streamlines for a = 5 are shown in figure 7.…”
Section: Resultsmentioning
confidence: 84%
“…Lyne's findings were verified experimentally by Bertelsen (1975) and Munsen (1975and Munsen ( , 1976. They investigated the nature of the steady secondary-flow component using flow-visualization techniques.…”
Section: Introductionmentioning
confidence: 89%
“…Numerical studies of toroidal pipes have shown that, under certain conditions, a four-vortex solution exists for both steady flow (Dennis & Ng 1982;Nandakumar & Masliyah 1982;Yanase, Gotoh & Yamamoto 1989) and unsteady flow (Lyne 1971;Zalosh & Nelson 1973). A stable four-vortex solution was also observed in the experimental work of Bertelsen (1975).…”
Section: Introductionmentioning
confidence: 89%